PENGEMBANGAN MESIN FERMENTASI ROTI MENGGUNAKAN PENDEKATAN VALUE ENGINEERING (VE) - Rachmad Hidayat; Anis Arendra; Sabarudin Akhmad (Spektrum Industri, 2014)
The purpose of this study improve engine performance by improving the fermentation of bread heat distribution patterns in the machine and increase energy use efficiency by reducing energy consumption of electricity grid using alternatives other energy sources. In this study, the calculation method used three expert assessment of each alternative posed is by using the fish bone diagram to diagnose the existing problems in fermentation machine. Histogram to determine the amount of costs required by each alternative are raised, based on factual data and by using the method of Analytic Hierarchy Process (AHP) to determine the criteria and weighting of each alternative based on the assessment of three experts. The results showed that one alternative energy source value, performance and cost of the best and competitive compared with other alternatives. Best alternative fermented bread machine is one with an alternative energy source without the use of automated systems gas pipeline. Key words : criteria, value fishbone diagram, histogram, fermentation machines